2020
DOI: 10.1002/jsfa.10666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary ferulic acid on growth performance, carcass traits and meat quality of heifers

Abstract: BACKGROUND: Ferulic acid is a natural occurring compound with antioxidant and antimicrobial bioactive properties, and recently was proposed as a new alternative growth promoter in meat-producing animals without changing meat quality parameters. The present study aimed to evaluate the impact of two doses of ferulic acid (FA) on the feedlot performance, carcass traits, and physicochemical and sensory characteristics of meat quality in commercial heifers. Ninety heifers (3/4 Bos taurus; n = 270; body weight = 480… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Studies related to the effects of FA supplementation on productive species are limited and inconsistent. Results of the present study agree with a previous study of finishing heifers supplemented with FA (2,250 or 4,500 mg FA d −1 ) where an increase of ADG and feed conversion was observed compared to non-supplemented animals [6]. Another study on ewe lambs reported an increase on wholesale cut yields when they were supplemented for 40 days with 250 mg kg −1 of FA under extreme heat stress [7].…”
Section: Growth Performance and Carcass Characteristicssupporting
confidence: 91%
“…Studies related to the effects of FA supplementation on productive species are limited and inconsistent. Results of the present study agree with a previous study of finishing heifers supplemented with FA (2,250 or 4,500 mg FA d −1 ) where an increase of ADG and feed conversion was observed compared to non-supplemented animals [6]. Another study on ewe lambs reported an increase on wholesale cut yields when they were supplemented for 40 days with 250 mg kg −1 of FA under extreme heat stress [7].…”
Section: Growth Performance and Carcass Characteristicssupporting
confidence: 91%
“…These parameters (pH, WHC, cooking loss, color, and WBSF) were maintained within the reported values for lambs [ 9 , 46 - 48 ]. The lack of effects on color parameters between groups is consistent with previous reports with FA supplementation [ 6 - 9 , 48 ]. It has been reported that phytochemicals that exhibited antioxidant properties could delay metmyoglobin formation by reducing myoglobin and lipid oxidation, improving meat color stability [ 5 , 49 ]; however, FA did not show any antioxidant properties in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of effects of FA in our results is in accordance with [ 9 , 10 , 30 ] findings. In contrast, Peña-Torres et al [ 6 ] found that by including 250 ppm FA in the diet of heifers, dressing weight and loin area were improved. In addition, previous studies have shown that phytochemicals and plant extracts did not alter carcass characteristics in fattening lambs [ 39 ].…”
Section: Discussionmentioning
confidence: 95%
“…The decrease in the growth performance can be explained by the hypothalamic–pituitary–adrenal-axis-associated antioxidant process, which induced anorexia [ 34 ]. It has been reported by Peña Torres that the supplementation of FA increases ADG in heifers [ 35 ]. Similarly, Yu found that the supplementation of FA in daily feed with oxidized fish oil showed a positive effect in farmed tilapia due to the antioxidative potential of FA [ 36 ].…”
Section: Discussionmentioning
confidence: 99%